UU Omnibus law yang Kontroversial - Munadhil Abdul Muqsith (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:In the midst of concern in dealing with the 2019 Corona Virus Disease (COVID-19) pandemic, the Indonesian House of Representatives (DPR) passed the Omnibus Law on the Job Creation Bill (Ciptaker) at the plenary session of the closing session of the trial period I for the 2020-2021 Session Year on October 5, 2020. Two of the nine Party factions rejected the ratification, namely the Prosperous Kedilan Party (PKS) and the Democrat Party (PD). Since it was passed by the DPR, currently, the hot ball is with the President. The President has 30 days to suppress or not press in accordance with Article 73 of Law No. 12 of 2011 on the formation of legislation. Of course, the public is anxiously awaiting the President's choice.Keyword: Omnibus law, Controversy Abstrak:Di tengah keprihatinan dalam menghadapi pandemi Corona Virus Disease 2019 (COVID-19), Dewan Perwakilan Rakyat (DPR) RI mengesahkan Omnibus Law RUU Cipta Kerja (Ciptaker) pada Rapat paripurna sidang penutupan masa persidangan I Tahun Sidang 2020-2021 pada 5 Oktober 2020. Dua dari sembilan fraksi Partai menolak pengesahan yakni Fraksi Partai Kedilan Sejahtera (PKS), Fraksi Partai Demokrat (PD). Sejak di sahkan DPR, saat ini, bola panas ada di Presiden. Presiden punya waktu selama 30 hari untuk menekan atau tidak menekan sesuai Pasal 73 UU No 12 Tahun 2011 tentang pembentukan perundang-undangan. Tentunya publik harap-harap cemas menunggu pilihan Presiden.Kata Kunci: Omnibus Law, Controversial